Transformasi kualitas air di Dusun Tlocor: Implikasi penggunaan ALPAMAL (Alat Pemurni Air Payau dengan Material Lokal) dalam kehidupan sehari-hari - Hermawan, Surya; Njo, Anastasia; Harjanti, Dhyah; Kawano, Yuka (Nur Science Institute, 2024)
Water is a primary necessity, but access to clean water remains limited, particularly in remote coastal regions of Indonesia. Therefore, a community empowerment initiative that implemented a brackish water purification device utilizing local materials (ALPAMAL) in Kedung Pandan Village, Jabon, Sidoarjo, through a service-learning approach. The program aimed to enhance the quality of life by facilitating access to clean water for daily household use, where brackish water is purified into potable water via ALPAMAL. The methodology commenced with surveys and observational studies to assess community conditions, followed by the assembly and installation of the ALPAMAL unit. Subsequently, a post-activity inauguration and resident survey were conducted. The results indicated that prior to ALPAMAL installation, it was characterized by high salinity, notable turbidity, and viscous consistency, rendering washing practices ineffective. Following the utilization of ALPAMAL, approximately 50% of respondents noted that the water was no longer sticky, while the remaining 50% reported that laundry became cleaner. All community partners perceived a notable transformation post-installation, with access to clean, sufficient water now available to meet daily requirements.